NaOH/pumice and LiOH/pumice as heterogeneous solid base catalysts for biodiesel production from soybean oil an optimization study - Mora, Joy Marie R.
Transesterification reaction of soybean oil with methanol was carried out to produce fatty acid methyl esters (FAME) using calcined alkali metal (Na and Li) supported by pumice silica as solid base catalyst.Pumice silica catalyst was activated by loading alkali metal ions to its surface via an ion-exchange method.Response surface methodology (RSM) in combination with Box-Behnken design (BBD) was used to methanol to oil molar ratio,reaction time,and catalyst concentration.Using the optimized sets of parameters,FAME yields using sodium and lithium silicate catalysts were 98.80% and 98.77% respectively.A pseudo-first order kinetic equation was applied characterized by several techniques such as X-ray diffraction (XRD),Fourier transform electron microscopy(SEM).In addition,the reusability of the catalyst was successfully tested in two subsequent cycles.